Lesson Study effectiveness for teachers' professional learning: a best evidence synthesis. Issue 4 (17th July 2019) - Willems, Iris; Van den Bossche, Piet
Abstract : Purpose: The purpose of this paper is to gather evidence for the effectiveness of Lesson Study (LS) for teachers' professional learning. Design/methodology/approach: A systematic review of relevant papers published between January 2010 and April 2018 was performed. To accomplish the best evidence synthesis, relevant studies were selected based upon well-chosen keywords and inclusion criteria. Afterwards, the quality of the remaining studies was assessed by using a critical appraisal checklist combined with a strength and weakness analysis. Data sources included relevant articles identified through digital searches on Education Research Information Centre and Web of Science, as well through snowball sampling and personal contacts. A total of five studies meeting inclusion criteria were retained for this review. Findings: These five studies describe LS as a powerful professional development approach because of its positive impact on teachers' professional learning. A significant improvement or change for knowledge, skills, behaviour and beliefs has been reported among teachers. Originality/value: Only studies with a design that shows high effectiveness were selected. The sample of relevant studies is currently small. As a consequence more large-scale and long-term research which illustrates the short and long-term effects of the LS approach on teachers' and students' learning is desirable.